As sentenças da Corte Interamericana de Direitos Humanos e a problemática da execução no direito brasileiro - Queiroz, Ana Paula Matos de (2018)
The present work is dedicated to the theme of Inter-American judgments in Human Rights matters, with emphasis on the issue of enforcement, also highlighting the case of compliance with decisions in Brazilian law. Therefore, the research turns to two distinct but directly related objects: the judgments of the Inter-American Court of Human Rights and the question of the enforcement of these decisions by domestic law. Thus, the bibliographical research was carried out, with a focus on doctrine, mainly Brazilian and Latin American, national legislation, international law and inter-American human rights jurisprudence. Regarding this aspect, it was preferred to read and analyze the judgments of the Inter-American Court itself, seeking to observe what wife the court on the subject addressed. In this scope, the problem of the adequacy between the Brazilian domestic law and the international human rights law was to approve the issue of compliance with judgments, and it was analyzed whether the internal procedure for the execution of inter-American human rights judgments is in favor of the Inter-American Court of Human Rights, based on the study of Supervisors of Compliance with Judgment of the Brazilian Cases. It was therefore sought to answer the question regarding the sufficiency of state conduct in executing the judgments of the Inter-American Court. In the end, the conclusion was reached that the fulfillment of the above-mentioned results shows that Brazil needs to review and improve its practices for internalizing inter-American judgments, and above all, it is necessary to approve national law that deals specifically with the issue of decision-making from international courts.